Optimization of Machine Learning Models for Jiwa Garuda in Predicting Geothermal Well Flow Rates - Pasaribu, Aldo (Yayasan Kita Menulis, 2025)
The accurate prediction of geothermal well flow rates is critical for optimizing resource utilization and ensuring sustainable energy production. This study focuses on the optimization of machine learning models, termed